Anti-VEGF combined with fufang xueshuangtong versus anti-VEGF monotherapy for wet age-related macular degeneration: A meta-analysis - Tingke Xie; Yanyan Lan; Chengming Chen; Jing Han (Pharmacological Research - Modern Chinese Medicine)
Purpose: To evaluate the effectiveness and safety of combining anti-VEGF and fufang xueshuangtong in the treatment of wet age-related macular degeneration (wet AMD). Methods: A systematic review of studies focusing on the efficacy and safety of the combined anti-VEGF and Fufang Xueshuantong therapy versus anti-VEGF monotherapy for wet AMD was conducted. This meta-analysis was performed based on a protocol registered in PROSPERO (CRD42024593135). The outcomes were reported as weighted mean differences (MDs) with corresponding 95 % confidence intervals (CI) or risk ratio (RR) with 95 % CI. Results: A total of 9 studies, involving 731 participants, were included. The MD for best-corrected visual acuity (BCVA) improvement, central macular thickness (CMT), and size of choroidal neovascularization (CNV) between the combination therapy and monotherapy groups were 7.37 (95 % CI [5.35 to 9.39]), −35.57 (95 % CI [−47.02 to −24.12]), and −1.81 (95 % CI [−2.56 to −1.07]), respectively. Additionally, the combination therapy group showed greater improvement in serum and ocular hemodynamics and had a lesser impact on intraocular pressure, and there was no significant difference in the incidence of adverse reactions between the two regimens. Conclusions: The combination of anti-VEGF therapy with Fufang Xueshuantong provides superior efficacy compared to anti-VEGF monotherapy in the treatment of wet AMD and is associated with an improved safety profile. However, further trials are needed to enhance the robustness and reliability of these findings.